GAMBARAN BUDAYA ORGANISASI: ANALISIS LITERATUR TEORITIS DAN EMPIRIS - Luh Nathania Ratnamaya Ratnamaya; Dinda Laily Machfudzoh; Naufal Putera Dianta (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to comprehensively examine the concept of organizational culture through a theoretical and empirical literature analysis of previous studies. Organizational culture is an important factor influencing individual behavior, employee performance, and overall organizational effectiveness. This study employed a literature review method using a Systematic Literature Review (SLR) approach combined with thematic analysis to identify key patterns and themes from previous studies. Data collection was conducted through a systematic search of academic databases using specific inclusion criteria, resulting in 30 relevant articles for analysis. The findings indicate that organizational culture has a significant influence on employee performance, job satisfaction, and organizational commitment. A strong and positive culture enhances productivity, strengthens employee loyalty, and creates a conducive work environment. In addition, an adaptive organizational culture supports organizational effectiveness in responding to change. Based on the literature analysis, it can be concluded that organizational culture is a strategic element in improving organizational performance and success. Therefore, developing a positive organizational culture is essential to support organizational sustainability and competitiveness.